أثر المرونة الاستراتيجية على الأداء التنظيمي دراسة ميدانية على شركات التأمين في محافظة طرطوس - شيحا أيمن; عبد الرحمن نسرين; يوسف علام (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تسعى منظمات الأعمال بشكل حثيث إلى تحسين وتطوير أدائها بما يضمن نموها واستمراها في السوق وخاصة في ظل المخاطرة وعدم التأكد والتي تؤثر سلباً على أداء تلك المنظمات فيما لو لم تقابل بآليات عمل تمكنها من مواكبة التغيرات الناتجة عن تلك الحالات. وقد هدفت هذه الدراسة إلى معرفة أثر المرونة الاستراتيجية على أداء شركات التأمين في محافظة طرطوس، من خلال دراسة ميدانية على شركات التأمين في مدينة طرطوس، وقد تم الحصول على البيانات من خلال استبانة مصممة لقياس المرونة الاستراتيجية، ولقياس الأداء الكلي بشقيه الكفاءة والفعالية، وزعت الاستبانة على المدراء ورؤساء الأقسام في الشركات محل الدراسة وتم استخدام برنامج التحليل الإحصائي(18) SPSS. أظهرت الدراسة وجود علاقة ذات دلالة إحصايئة بين (المرونة الاستراتيجية المبادرة – المرونة القائمة على رد الفعل) وكفاءة الأداء في شركات التأمين محل الدراسة، حيث بلغت قيمة معامل الارتباط بين المتغيرات المستقلة والمتغير التابع الأول (الكفاءة)r=0.569 وهو ارتباط موجب، ومعامل التحديد 32.3%r2= حيث يمكن القول أن المتغير المستقل(المرونة الاستراتيجية) يفسر 32.3% من التغيرات الحاصلة في المتغير التابع (الكفاءة) ويمكن رد النسبة المتبقية إلى عوامل أخرى لم تأخذها الدراسة بالاعتبار، كما أظهرت الدراسة وجود علاقة ذات دلالة إحصايئية بين (المرونة الاستراتيجية المبادرة – القائمة على رد الفعل) و فعالية الأداء في شركات التأمين محل الدراسة. حيث بلغت قيمة معامل الارتباط بين المتغيرات المستقلة والمتغير التابع االثاني (الفعالية)r=0.74 وهو ارتباط موجب، ومعامل التحديد 54.8% r2= أي أن المتغير المستقل(المرونة الاستراتيجية) يفسر ما مقداره 54.8% من التغيرات الحاصلة في المتغير التابع(الفعالية) . Organizations continuously seek to improve their performance in order to ensure their growth and stability in the market, especially in light of the risk and uncertainty which both of them have an adversely affects on the performance of organizations. Consequently, organizations have to adapt mechanisms enable them coping with uncertainty situation and its consequences. This study aimed to investigate the impact of the strategic flexibility on the performance of insurance companies in Tartous, it has been getting the data had collected through a questionnaire which designed to measure the strategic flexibility, and to measure overall performance (efficiency and effectiveness), questionnaire had distributed to managers and heads of departments at insurance companies in Tartous city. SPSS (18) was used for data analyzing. The study showed a significant relationship between both (initiative strategic flexibility – reaction flexibility) and efficient performance in insurance companies , the value of the correlation coefficient between independent variables and the dependent variable (efficiency) was r= 0.569, (a positive correlation), and the coefficient of determination r 2 = 32.3%, that means the independent variable (strategic flexibility) explains 32.3% of dependent variable changes of (the efficiency) and remainder Complement ratio relates to other factors did not note by this study. In addition to that, study showed a significant relationship between (both (initiative strategic flexibility – reaction flexibility) effectiveness at insurance companies, the value of the correlation coefficient between independent variables and the dependent variable (effectiveness) was r= 0.74, a positive correlation, and the coefficient of determination r 2 =54.8%. That means the independent variable (strategic flexibility) explains 32.3% of dependent variable changes of (the effectiveness) and remainder Complement ratio relates to other factors did not note by this study.